Improving EFL Students' English Pronunciation by Using the Explicit Teaching Approach - Pardede, Parlindungan (JET (Journal of English Teaching), 2018)
Due to several reasons, pronunciation instruction had often been neglected in English as a Foreign Language (EFL) classes. Consequently, many EFL learners always find it difficult to speak confidently because of their poor pronunciation. This study is a three-cycled action research aimed at enhancing EFL students' pronunciation by using the explicit teaching approach. The participants were 21 students majoring in English Education at Universitas Kristen Indonesia who attended Integrated Skills IV class in the even semester of 2015/2016 Academic Year. The participants were provided with special practices on pronunciation, including watching a video or listening to English expressions containing elements of English pronunciation difficult to them, drillings the elements, recording and transcribing their utterances, and comparing the transcriptions with those of native speakers'. Data were collected through tests and questionnaires. The results revealed that the explicit teaching approach enhanced the participants' English pronunciation skills, as shown by the increase in their average scores in the four tests administered during the implementation of the actions. The survey results revealed that for the participants the approach was interesting, helped pronunciation development, and increased self-confidence in English speaking. Keywords: action research, pronunciation, explicit teaching